Digitalisasi Wisata Pantai Ekasoghi Sumenep Melalui Media Sosial - Syamsul Arifin; Evi Dwi Hastri; Pathorrahman Pathorrahman; Wilda Rasaili (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
Social media has a big role in promoting ekasoghi beach tourism. Promotion through social media tiktok, Instagram and Facebook is a strategy carried out by Ekasoghi beach tourism managers in an effort to increase of the visitors. Open access to information is expected to provide information to potential tourists to obtain accurate information according to the information needed. In addition, the presentation of information through social media is able to persuade visitors so that in the next process it encourages them to visit Ekasoghi beach tourist destinations. This study uses a qualitative approach to the method of collecting observational data. The research results show that 1) many destinations have become viral or known to the wider community because the destinations difused on social media, 2) Tiktok is used to share cinematic videos and Ekasoghi beach vlog videos, 3) Instagram is used to disseminate various facilities on Ekasoghi Beach, 4) Facebook is used as a marketing medium to a wide audience to promote various Ekasoghi beach tourism products.